Alert - Patterson, James (Century, 2015)
New York has seen more than its fair share of horrific attacks, but the city is about to be shaken in a way it never has before. After two devastating catastrophes in quick succession, everyone is on edge. Detective Michael Bennett is assigned to the case and given the near impossible task of hunting down the shadowy terror group responsible.